Design of Internship Student Management Information System with Software Development Life Cycle Approach - Fakhira, Indah Naurah; Derta, Sarwo; Musril, Hari Antoni; Okra, Riri (Knowbase : International Journal of Knowledge in Database, 2023)
This research is motivated by the absence of an information system concerning the placement of student internships. This is attributed to the diverse backgrounds of students at the H. Agus Salim Institute of Technology and Business (ITB), comprising three different classes. For regular morning students, internship placements can be tailored to their field of study. However, for evening students (regular two) and weekend students (regular three), who are individuals already employed in government institutions and private companies, determining suitable internship locations becomes challenging. This is because the tasks performed in these institutions and companies may not align with the academic disciplines studied by the students during their academic tenure. In the design of this internship information system, the researcher adopts the Incremental model, which is one of the models in the Software Development Life Cycle (SDLC). Functional suitability testing, compatibility testing, usability testing, and validity testing were conducted on the internship management information system. The test results, carried out by one expert, yielded a functional suitability score of 94%, categorized as excellent. The capability test, also conducted by one expert, resulted in a score of 80%, categorized as very good. Usability testing, conducted by seven experts, yielded a score of 80.6%. Validity testing, carried out by three validators, resulted in a score of 0.86, categorized as highly valid.